PI3K Class II [alpha] Controls Spatially Restricted Endosomal PtdIns3P and Rab11 Activation to Promote Primary Cilium Function - Franco, I.; Gulluni, F.; Campa, C.; Costa, C.; Margaria, J.; Ciraolo, E.; Martini, M.; Monteyne, D.; De Luca, E.; Germena, G.; Posor, Y.; Maffucci, T.; et al. (Cell Press, 2014)
Multiple phosphatidylinositol (PtdIns) 3-kinases (PI3Ks) can produce PtdIns3P to control endocytic trafficking, but whether enzyme specialization occurs in defined subcellular locations is unclear. Here, we report that PI3K-C2a is enriched in the pericentriolar recycling endocytic compartment (PRE) at the base of the primary cilium, where it regulates production of a specific pool of PtdIns3P. Loss of PI3K-C2a-derived PtdIns3P leads to mislocalization of PRE markers such as TfR and Rab11, reduces Rab11 activation, and blocks accumulation of Rab8 at the primary cilium. These changes in turn cause defects in primary cilium elongation, Smo ciliary translocation, and Sonic Hedgehog (Shh) signaling and ultimately impair embryonic development. Selective reconstitution of PtdIns3P levels in cells lacking PI3K-C2a rescues Rab11 activation, primary cilium length, and Shh pathway induction. Thus, PI3K-C2a regulates the formation of a PtdIns3P pool at the PRE required for Rab11 and Shh pathway activation.